Sociological Analysis of Students Lifestyles and Health During University Studies - T.A.Polaykova, A.S.Losev, S.G.Cemova, S.V.Mihajlova, K. A.Vlasova, Y. G. Kuzmichev, T.V.Sidorova, (Social Science Learning Education Journal, 2017)
The article deals with the results of a study of 430 studentsâ lifestyle and their orientation towards health protection during the process of professional formation at the University. During the period of study, the studentsâ lifestyle undergoes significant changes: reduced amount of time spent on homework, increased the number of students who combine studies with work, reduced physical activity, increased proportion of students with excessive body mass, increased primary morbidity and prevalence of smoking. The physical health of young people is influenced mostly by the level of physical activity and the bodys resistance to catarrhal diseases. Monitoring the indicators of lifestyle and health allows students to assess the effectiveness of preventive and rehabilitation measures and develop scientifically based health-improving programs.Key words: students, health, lifestyle, time management, physical education, morbidity, smoking, nutrition